MENANAMKAN KECERDASAN SPIRITUAL ANAK USIA DINI MELALUI PENDEKATAN â€œNURANIâ€ - Budiyanti, Nurti; Komariah, Kokom Siti; Parhan, Muhamad; Islamy, Mohammad Rindu Fajar; Nugraha, Risris Hari (Tunas Siliwangi, 2022)
Education is the process of developing the potential God gives to each child as a subject. The reality, the potential God has not been able to develop optimally in order to strengthen the spiritual aspect of children. There needs to be an effective approach to instill spiritual intelligence in children. Child education can be considered effective if educators have good competence and are capable of developing different approaches in the learning process. Moreover, early childhood need a special approach in embedding Islamic values in accordance with the growth and development. In this study, researchers sought to formulate a â€œNURANIâ€ as an accepative solution in instilling the spiritual intelligence of early childhood. The study uses a qualitative approach through analytical methods. Based on the findings and analysis in the study, the "NURANI" approach is seen as a child-friendly approach in order to improve spiritual intelligence. The steps of implementing the approach â€œNURANIâ€ is to give advice on a lot, give a spirit in a creative way, give reward and punishment both materially, verbally and non-verbal, provide learning in a dialogue, provide a ruhani experience by the imposition of Islamic values and give many examples both in speech and in action. The purpose of the implementation of this approach is to instill spiritual intelligence in the child in the form of consciousness in conducting Islamic law, discipline in practicing Islamic values and feel happy to do ritual worship in daily life